Real-time density feedback control in ADITYA-U Tokamak. (1st June 2022) - ; Patel, K.; Nagora, U.C.; Joshi, H.C.; Pathak, S.K.; Jadeja, K.A.; Patel, K.M.; Virani, C.; Patel, A.; Tanna, R.L.; Kumar, R.; Aich, S.; et al.
Abstract: A real-time density feedback control system with a 100 GHz heterodyne interferometer has been designed, developed, and commissioned in ADITYA-U tokamak. It consists of three subsystems i.e. density measurement, feedback control, and gas fuelling. A proportional feedback controller is configured in voltage amplitude mode to operate the piezo valve for gas injection. Experiments are performed during plasma discharges to achieve a predefined density evolution as well as constant density. Stickiness of the piezo valve restricts the temporal response of the valve. It is required to minimize during the plasma discharge for a fast density response which is achieved by a short preceding voltage pulse known as a stick pulse. This paper describes the implementation of a real-time density feedback control system which is successfully validated using another existing 140 GHz interferometer system in ADITYA-U. Moreover, the developed system consumes low power, is cost-effective and re-programmable, can be easily upgraded, and provides interlock with plasma parameters.